Determinants of the poor household decision to own Micro-Small Enterprise (MSEs) - Prijanto, Whinarko Juli; Sugiharti, Rr. Retno; Khabibah, Nibras Anny; Astutik, Erni Puji (JEJAK, 2024)
Household empowerment is an effort to increase family income, especially for poor households. Entrepreneurial activities in the household are expected to encourage independence and social mobility in poor households. This novel research analysed the decision-making behaviour of households owning a business through the probability function of micro and small business owners in poor households in Magelang City. The study will have implications for the design of policy planning related to poverty alleviation, especially regarding increasing entrepreneurship in poor households. Using the 2019 SUSEE database obtained from the Government of Magelang, this study can be concluded that the higher the age and education of the head of a household the greater the opportunity to decide to own a business. The main factor that encourages poor households to own a business is the ease of access to capital. The research findings show that households that have access to credit are proven to be more motivated to own a business. In addition, the more dominant family members have cell phones, the more likely a household is to own a business. From this research, the policy implications that can be carried out are intensifying and ease of providing business capital for micro-enterprises, providing training and coaching, especially in starting businesses for poor households based on simple technology. Owning MSEs has the potential and opportunity to improve the welfare of poor households through business ownership in the form of micro and small businesses.